Climate change and vector-borne diseases: a regional analysis - Andrew K. Githeko; Steve W. Lindsay; Ulisses E. Confalonieri; Jonathan A. Patz (Bulletin of the World Health Organization, 2000)
Current evidence suggests that inter-annual and inter-decadal climate variability have a direct influence on the epidemiology of vector-borne diseases. This evidence has been assessed at the continental level in order to determine the possible consequences of the expected future climate change. By 2100 it is estimated that average global temperatures will have risen by 1.0-3.5 °C, increasing the likelihood of many vector-borne diseases in new areas. The greatest effect of climate change on transmission is likely to be observed at the extremes of the range of temperatures at which transmission occurs. For many diseases these lie in the range 14-18 °C at the lower end and about 35-40 °C at the upper end. Malaria and dengue fever are among the most important vector-borne diseases in the tropics and subtropics; Lyme disease is the most common vector-borne disease in the USA and Europe. Encephalitis is also becoming a public health concern. Health risks due to climatic changes will differ between countries that have developed health infrastructures and those that do not. Human settlement patterns in the different regions will influence disease trends. While 70% of the population in South America is urbanized, the proportion in sub-Saharan Africa is less than 45%. Climatic anomalies associated with the El Niño-Southern Oscillation phenomenon and resulting in drought and floods are expected to increase in frequency and intensity. They have been linked to outbreaks of malaria in Africa, Asia and South America. Climate change has far-reaching consequences and touches on all life-support systems. It is therefore a factor that should be placed high among those that affect human health and survival.